Kepuasan Peserta Event Hunting Foto di 5 kota di Indonesia (dalam ruang lingkup ekonomi kreatif) (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2016)
Photography is one of the 14 sub creative economy that has been set in the Presidential Decree No. 6 of 2009, on the Creative Economy Development instructing the President to the Minister, Head of Government Institution Non-Department, all the governors, regents/ mayors are essentially in order to support the development policy of Economic creative years 2009-2015, particularly in the development of economic activities based on the creativity, skill, creativity and inventiveness to develop and implement an action plan to support the successful development of the creative economy. Additionally, based on Presidential Decree No. 92 / 2011 on December 21, 2011, has established the Ministry of Tourism and Creative Economy with the vision to realize the welfare and quality of life in Indonesia by moving the tourism and creative economy. This study aims to determine the relationship and the influence of marketing mix on customer satisfaction / participant hunting event, which was held in six cities in Indonesia. The method used is descriptive and associative / relationship, using two independent and dependent variables and Likert scale with five levels of measurement and data analysis through test reliability, validity, correlation and simple linear regression. The results found that the average value of the most dominant both in the marketing mix and customer satisfaction / participant is in a product with a mean value of 4.5 on a sub-product variable in the marketing mix and a mean value of 4.4 on a sub variable products in the customer satisfaction / participant. The relationships in the direction of a positive relationship with the level of relationship is very strong (0.862) and the successful marketing mix affects 74.3% on customer satisfaction / participant.